Proceedings of the 17th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2014
DOI: 10.1145/2531602.2531661
|View full text |Cite
|
Sign up to set email alerts
|

How players value their characters in world of warcraft

Abstract: Characters in games such as World of Warcraft allow players to act in the game world and to interact with others. Game characters and avatars are a mediated form of selfrepresentation for the player, but some research suggests that players also view characters in other ways that have to do with the kinds of value that the characters provide. To better understand the ways that players value their characters in an online environment, we carried out a semistructured interview study of twenty World of Warcraft pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…World of Warcraft is a popular fantasy themed MMORPG familiar to games research in HCI [10,17,23,30]. In this study we examined the culture and practices of players of World of Warcraft who identified themselves as 'raiders' and engaged in 'progression raiding' (see below).…”
Section: Group Play and Progression Raiding In World Of Warcraftmentioning
confidence: 99%
“…World of Warcraft is a popular fantasy themed MMORPG familiar to games research in HCI [10,17,23,30]. In this study we examined the culture and practices of players of World of Warcraft who identified themselves as 'raiders' and engaged in 'progression raiding' (see below).…”
Section: Group Play and Progression Raiding In World Of Warcraftmentioning
confidence: 99%
“…For example, Birk et al [7] revealed that avatar customization stimulates player identification, leading to increased autonomy, immersion, invested effort, enjoyment, and positive affect. Livingston et al [21] interviewed twenty World of Warcraft [9] players with the goal of investigating what kind of value their game characters provided. Tondello et al [32] and Toups et al [33] built on their work to examine why players value and collect a diversity of game objects, including but not limited to characters.…”
Section: Player Preferences Based On Game Featuresmentioning
confidence: 99%
“…We lack a clear understanding of players' collecting behaviors and how players perceive the value of their digital game objects. Prior research has explored how players value digital game characters (e.g., [20]) and general digital collections (e.g., [16,17,36]), yet questions remain about how players value digital game objects. We surveyed over 180 gamers about their digital game object collecting practices.…”
Section: Introductionmentioning
confidence: 99%
“…With this manual, we are able to understand the composition of players' collections. We connect our digital object types with prior work on digital character value (e.g., [20]) to understand why players value digital game objects and what drives them to collect. Through our data, we develop an understanding of why players collect digital game objects, why digital game objects are valued, how sociality plays a role in digital game object collections, and how players compose their digital game object collections.…”
Section: Introductionmentioning
confidence: 99%